Comparative study of wild-type and rd10 mice reveals transient intrinsic optical signal response before phosphodiesterase activation in retinal photoreceptors. Issue 4 (February 2020) - Lu, Yiming; Kim, Tae-Hoon; Yao, Xincheng
Transient intrinsic optical signal (IOS) has been observed in stimulus-evoked retinal photoreceptors. This study is to compare IOS changes in wild-type and retinal degeneration 10 (rd10) mouse retinas, to evaluate the effect of cyclic guanosine monophosphate phosphodiesterase on photoreceptor-IOS. Time-lapse near-infrared light microscopy was employed to monitor the spatiotemporal dynamics of the IOS responses in freshly isolated retinas activated by visible light stimulation. Comparative IOS recordings were conducted at postnatal days 14 (P14) and P16. At P14, intrinsic optical signal magnitudes and spatiotemporal dynamics in wild-type and rd10 retinas were similar, indicating that the phosphodiesterase deficiency in rd10 did not affect the formation of photoreceptor-IOS. At P16, IOS magnitude in rd10 significantly decreased compared to that in wild-type, suggesting the IOS sensitivity to the photoreceptor degeneration in rd10. Our experimental results and theoretical analysis indicate that early disc-based stages of the phototransduction cascade before the activation of phosphodiesterase may contribute to the formation of the photoreceptor-IOS responses; and the IOS can be a sensitive biomarker for objective assessment of retinal function. Impact statement: Comparative study of wild-type and rd10 mice was implemented to reveal that transient intrinsic optical signal (IOS) was initiated before the phosphodiesterase activation in stimulus-activated photoreceptors and the IOS magnitude was sensitive to photoreceptor degeneration. The photoreceptor-IOS promises a noninvasive biomarker for objective assessment of age-related macular degeneration, retinitis pigmentosa, and other eye diseases that can produce photoreceptor dysfunctions.